1975
DOI: 10.1161/01.cir.52.2.333
|View full text |Cite
|
Sign up to set email alerts
|

Clinical conference: De subitaneis mortibus. XIII. Multifocal Purkinije cell tumors of the heart.

Abstract: SUMMARYMultifocal Purkinje cell tumors were found in the heart of a nine-month-old black female infant who died with arrhythmias which had become progressively more frequent and severe until they were completely intractable. The Purkinje cell tumors were composed of exactly the same type of cells found in the left bundle branch and the right bundle branch, and they were also located in the expected region of the His bundle. In none of these locations were these Purkinje cells forming normal longitudinally orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…The cells showed no proliferative activity nor did they seem to undergo differentiation towards mature cardiomyocytes. Thus, our results do not support the hypothesis of defective maturation of cardiomyocytes of the Purkinje system [2,5,6,25]. On the other hand, we found that the altered cells were apoptotic, i.e., dead cells, pointing towards a degenerative acute or chronic process.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The cells showed no proliferative activity nor did they seem to undergo differentiation towards mature cardiomyocytes. Thus, our results do not support the hypothesis of defective maturation of cardiomyocytes of the Purkinje system [2,5,6,25]. On the other hand, we found that the altered cells were apoptotic, i.e., dead cells, pointing towards a degenerative acute or chronic process.…”
Section: Discussioncontrasting
confidence: 99%
“…Increased interstitial infiltration Occasional sparse interstitial infiltration LCA Increased interstitial infiltration Occasional sparse interstitial infiltration Mast cells Increased interstitial infiltration Normal residents cells their ultrastructural features point to a possible kinship with the Purkinjecells of the conduction system [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age of onset ranges from birth to 2 years, and one case with intrauterine tachycardia has been reported [Kearney et al, 19871. In the f i s t 26 cases reported [Wegman and Egbert, 1935;Voth, 1962;Ross and Belton, 1968;Reid et al, 1968;MacMahon, 1971;Haese et al, 1972;Kauffman et al, 1972;Bove and Schwartz, 1973;Deacon et al, 1974;James et al, 1975;Ferrans et al, 1976;Bruton et al, 1977;Witzleben and Pinto, 1978;Amini et al, 1980;Radford and Chalk, 1980;Silver et al, 1980;Becker and Anderson, 1981;Zimmerman et al, 1982;Saffitz et al, 19831, the diagnosis was made at necropsy, and no child survived longer than 9 months after onset of dysrhythmias. McGregor et al, [1984] reported the first case to be diagnosed during life and treated successfully with the removal of a single focus of oncocytic cells.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Currently, electrophysiologic mapping may localize the abnormality so that curative surgical excision can be performed for this previously fatal condition. 14 In this study we present the morphologic findings in 11 recently treated patients (nine of whom survived), review previously reported cases, and discuss concepts of pathogenesis of this peculiar myocardial lesion.…”
mentioning
confidence: 99%